Análise epistemológica das dissertações e teses defendidas no Programa de Pós-Graduação em Educação Especial da UFSCar: 1981-2002. - Silva, Régis Henrique dos Reis (2004)
This study has as an object of analysis the dissertations and thesis developed in the Post Graduation Program in Special Education of the Universidade Federal de São Carlos (PPGEEs/UFSCar), from 1981 to 2002. Its general aim is to analyse, from the methodological approaches, the epistemological implications of the dissertations and thesis produced, considering their inter-relations with the social-political and economical factors. In this perspective, we tried to explicit how these factors stablish contact with the dissertations and thesis presented in PPGEEs/UFSCar. This theoretical-methodological procedure implied in the search of dynamic articulation of internal analyses (logical- gnoseological and methodological) and external (historical-social), of the investigated production. In the 27 analysed documents, 88,9% of them adopted the empirical-analytical approach, which were predominant in all the four phases of curricular organization of the Program. The phenomenological-hermeneutical researches represented 11,1% of the sample. Meanwhile, the critical-dialectical approach was not adopted in any of the analysed studies. We noted that, in spite of some variations, commom epistemological assumptions are presented in the criteria of cientificity which are the basis of the researches, in the manners they relate subject and object in the cognitive process of knowledge, and in the conceptions of casuality, science, human being, history, reality, education/special education and deficiency, according to the methodological approach which guide them. We verify that in the empirical-analytical researches, the dominant understanding of science is related to the principles of quantification and mathematization of the phenomena. Based in the statistical parameters, in the search for objectivity of the knowledge, in the distance from the researcher to the object of study, among other characteristics that point to a view of science centred to the positivist vertent. In the other hand, for the phenomenological-hermeneutical researches, the science consists in the comprehension of phenomena, from the collected data in many manifestations, in the elucidation of unclear mechanisms, of implications, of contexts in which these phenomena are based. The researches of this group do not trust in the immediate percpetion of object that only promote the appearence. However, from that perception and through the interpretation, the essence of the phenomena is discovered. The phenomenological-hermeneutical researches have as their main criteria of scientific validation, the interpretative reflection of the researcher supported by the intersubjective consensus (philosophical principles of phenomology-hermeneutic). Considering the articulations between the logical and the historical, we verifiy the predominance of empirical-analytical approach in the analysed documents and it is related to social-political and economical factors, specially, to the Post graduation implanted in the country, as well, with the internal characteristics of PPGEEs/UFSCar, mainly, by the epistemological matrix predominant in the Departament of Psychology, responsible for the orientation of activities which are developed by the Program. From the concrete possibilities of changes in the structure and in the internal relations of the PPGEEs/UFSCar, as well as the relevance and the social commitment that it performs in relation to the qualitative progress of the produced knowledge in the Brazilian Special Education, it suggested that the ways for the formation of researcher about the theoretical, philosophical and epistemological of scientific research would be amplied and diversified. That has the objective of supplying elements so that the knowledge produced in the Special Education, may be understood in a wider way, and mainly, contribute for the superation of numerous problems existents in the reality of people with special educational needs.